1994
DOI: 10.2527/1994.723622x
|View full text |Cite
|
Sign up to set email alerts
|

Improved soybean protein sources for early-weaned pigs: I. Effects on performance and total tract amino acid digestibility

Abstract: Seventy-two Yorkshire pigs weaned at 21 d of age were allotted to one of seven treatments with different protein sources serving as the primary lysine source at the expense of dried skim milk. Protein sources were dried skim milk (DSM), two isolated soybean proteins (ISP), three soybean protein concentrates (SPC), and 48.5% soybean meal (SBM). Average daily gain (ADG) and feed efficiency (G:F) were greater (P < .05) for pigs fed the DSM diet, the two ISP diets, or the three SPC diets during the first 2-wk peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
3
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 0 publications
9
32
3
5
Order By: Relevance
“…Os resultados apresentados neste experimento não estão em acordo com Grant et al (1990) e Sohn et al (1994a), que não observaram diferença no ganho de peso entre leitões alimentados com proteína láctea e leitões que receberam isolado protéico de soja. No entanto, Newport & Keal (1982) e Walker et al(1986) observaram que a substituição de 70% a 74% da Figura 2 -Níveis de substituição do leite em pó desnatado pelo isolado protéico de soja sobre o ganho de peso de leitões desmamados.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os resultados apresentados neste experimento não estão em acordo com Grant et al (1990) e Sohn et al (1994a), que não observaram diferença no ganho de peso entre leitões alimentados com proteína láctea e leitões que receberam isolado protéico de soja. No entanto, Newport & Keal (1982) e Walker et al(1986) observaram que a substituição de 70% a 74% da Figura 2 -Níveis de substituição do leite em pó desnatado pelo isolado protéico de soja sobre o ganho de peso de leitões desmamados.…”
Section: Resultsunclassified
“…Aproximadamente um terço da proteína em uma dieta com leite como única fonte protéica, pode ser substituído pelo isolado protéico de soja sem afetar o desempenho (Newport & Keal, 1982). Grant et al (1990) estudaram o efeito da substituição de 20% da proteína da dieta totalmente láctea pelo isolado protéico de soja para leitões alimentados com dietas líquidas (15%MS) e observaram que o ganho de peso diário não diferiu entre as dietas, resultados comprovados por Sohn et al (1994a), em estudo com leitões desmamados aos 21 dias e criados até os 28 dias de idade, alimentados com leite desnatado em pó (40% da dieta) ou isolado protéico de soja solúvel e insolúvel a 20,29% da dieta ou concentrado protéico de soja (25,09%). Neste estudo, os autores relataram ainda que as três fontes protéicas supracitadas foram superiores em relação ao ganho de peso e à eficiência alimentar quando comparadas com o farelo de soja (24,12% da dieta), porém esta diferença no desempenho dos animais desapareceu após três semanas subseqüentes ao teste, quando todos os animais receberam a mesma ração comercial.…”
Section: Introductionunclassified
“…The authors have not found any published report comparing the effects of diets based on SPC and SBM on growth performance and nutrient digestibility in IB pigs. In conventional white pigs, most available data favors the inclusion of SPC in the diet at the expense of SBM (Sohn et al, 1994), probably because of the lower ANF content of SPC. Also, Yang et al (2007) reported that the inclusion of 8% SPC in the diet, in substitution of similar amounts of HP-SBM, improved growth performance of pigs from 23 to 58 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, glycinin and β-conglycinin are potential antigenic and allergenic proteins that might cause villus atrophy and crypt hyperplasia and reduce the absorptive capacity of the small intestine of the pigs (Li et al, 1990). Soya protein concentrates (SPC) had lower ANF and non-starch polysaccharides content than SBM and therefore, SPC contain more CP, which should be more digestible, than the corresponding meal (Sohn et al, 1994). Consequently, the inclusion of SPC in the diet in substitution of SBM should result in improved intestinal morphology, nutrient utilization and growth performance of weanling pigs.…”
Section: Introductionmentioning
confidence: 99%
“…A imaturidade digestiva, a insuficiente secreção ácida, juntamente com os fatores estressantes do desmame, evidenciam-se pela má absorção de nutrientes e ocorrência de diarréia (ETHERIDGE et al, 1984;SOHN et al, 1994), podendo ocasionar distúrbio no balanço da flora intestinal e resultar em baixo desempenho. (TRINDADE NETO et al, 2003).…”
Section: Lista De Tabelasunclassified